Belief States in Criminal Law - Macleod, James A. (2016)
Belief-state ascription—determining what someone “knew,” “believed,” was “aware of,” etc.—is central to many areas of law. In criminal law, the distinction between knowledge and recklessness, and the use of broad jury instructions concerning other belief states, presupposes a common and stable understanding of what those belief-state terms mean. But a wealth of empirical work at the intersection of philosophy and psychology—falling under the banner of “Experimental Epistemology”—reveals how laypeople’s understandings of mens rea concepts differ systematically from what scholars, courts, and perhaps legislators, have assumed. As implemented, mens rea concepts are much more context-dependent and normatively evaluative than the conventional wisdom suggests, even assuming that jurors are following jury instructions to the letter. As a result, there is less difference between knowledge and recklessness than is typically assumed; jurors consistently “over”-ascribe knowledge to criminal defendants; and concepts like “belief,” “awareness,” and “conscious disregard” mean different things in different contexts, resulting in mens rea findings systematically responsive to aspects of the case traditionally considered irrelevant to the meaning of those terms. This Article provides the first systematic account of the factors driving jurors’ ascriptions of the specific belief states criminal law invokes. After surveying mens rea jury instructions, introducing the Experimental Epistemology literature to the legal literature on mens rea, and examining the implications of that literature for criminal law, this Article considers ways to begin bridging the surprisingly large gap between mens rea theory and practice